"Here One Moment… and Gone the Next?" Remittance as a Social Visibility Tool. Issue 3 (27th May 2016) - Harper, Robin A.; Zubida, Hani
Abstract : Human labor is as much an export as any good. Remittances are a critical source of income for left‐behind families and communities. Transnational labor migrants often describe themselves as 'invisible': neither present in the lives of left‐behind families nor members of the receiving community. Building on social remittances literature, we argue that remittances serve as a remedy for this 'invisibility.' Through analysis of interviews with 26 temporary labor migrants from 11 countries resident in Israel, we find remittances can render migrants visible to transnational families and provide identity benefits to labor migrants. If visibility benefits decline because of familial role changes, reduced value as a remitter, cost exceeding benefits or because contracting partners change, remittance practices will change. Contrary to previous literature, our findings show that remittances decisions are dynamic, revealing why remittances practices change and even cease. Findings have implications for understanding the multibillion‐dollar remittances industry and immigrant incorporation.